The Impact of Plant Closures or Deindustrialization on Local Labor Relations in Small and Mono-industrial United States Cities - Ibrahim Niftiyev (Proceedings: TNKU FEAS II. International Symposium on Labour Economics and Industrial Relations, December 06, 2024, 2024)
Manufacturing has long been regarded as a primary engine of growth and economic development in developed countries, even as the rise of the service sector and deindustrialization have become increasingly prevalent since the 1970s. Despite these shifts, the manufacturing sector remains a significant contributor to employment and a major force in industrial relations. However, small cities and towns are particularly vulnerable to the impacts of deindustrialization, as plant closures can lead to severe socioeconomic consequences in communities across the United States (US) that are shaped as single-or mono-industrial towns or cities. While shutdowns are often driven by economic rationales such as cost and capacity optimization, efficiency, competitiveness, and globalization, workers and other residents in these towns experience substantial challenges following plant closures, including unemployment, social and psychological distress, forced migration, poverty and homelessness. These issues are captured by various local news programs uploaded to YouTube, offering real-time insights into the impacts on these communities. This paper aims to analyze these videos as a secondary data source to provide a more nuanced understanding of the socioeconomic consequences of plant closures, beyond mere statistical fluctuations. The primary qualitative data set consists of 15 videos, which were analyzed through qualitative content analysis (QCA), thematic analysis (TA) and narrative analysis. Among the 14 mono-industrial and small towns studied, the smallest had 155 residents, while the largest had approximately 61,000 residents. The findings indicate that mono-industrial towns are highly vulnerable to the exodus of a single economic player (so-called "the integrator"). The lack of alternative employment opportunities and low levels of industrial diversification jeopardize the well-being of residents, often forcing them to leave and risking the creation of ghost towns. The negative impacts extend to closures in the tertiary sector, disruptions in workers' personal lives, psychological distress and interruptions in schooling for families. These findings will be valuable for anyone interested in understanding the effects of plant closures on small towns across the US, providing insights for policymakers and contributing to academic discourse on the socioeconomic dimensions of small-scale deindustrialization. Compared to econometric studies and highly stylized academic research, qualitative, human-centered perspectives remain scarce in academia, highlighting gaps in knowledge and methodology in the study of industrial relations.
Keywords: 330; deindustrialization; factory shutdown; labor relations; media; mono-industry; small cities; thematic analysis; towns; urban planning; qualitative content analysis; US economy